Flagship Species – Flagship Problems: recovery of species at risk and the conservation of biodiversity in Canada 1 This introduction is part of the virtual symposium “Flagship Species – Flagship Problems” that deals with ecology, biodiversity and management issues, and climate impacts on species at risk and of Canadian importance, including the polar bear ( Ursus maritimus), Atlantic cod ( Gadus morhua), Piping Plover ( Charadrius melodus), and caribou ( Rangifer tarandus). - Boates, J. Sherman; Fenton, M. Brock (Canadian Journal of Zoology, 2011)
This is an Introduction to a series of review articles, entitled Flagship Species – Flagship Problems, that identify, review, and address key problems, solutions, and contradictions linked to conservation and recovery of four iconic species at risk in Canada (polar bear, Ursus maritimus Phipps, 1774; Atlantic cod, Gadus morhua L., 1758; Piping Plover. Charadrius melodus Ord, 1824; caribou, Rangifer tarandus (L., 1758)), as well as one review article dealing with the more systemic impacts of habitat loss and degradation. The reviews are cast in the context of the broader challenge of maintaining and restoring biodiversity.